Implementasi Program Mentoring dalam Meningkatkan Kemampuan Membaca Al Qur’an Peserta Didik Kelas VII di SMP PGII 1 Bandung - Tegar Maulana; Aep Saepudin; Dinar Nur Inten (UNISBA Press, 2024)
Abstract. This research aims to determine the planning, implementation, evaluation, and supporting and inhibiting factors in the mentoring program at SMP PGII 1 Bandung. The method used is descriptive qualitative with data collection techniques through interviews and documentation. The research results show that this mentoring program can improve the ability to read the Qur'an through 1) plans made with the aim of eradicating Qur'an illiteracy and improving the ability to read, write and understand the Qur'an, as well as arranging a time, place and resource schedule , 2) the implementation is carried out on Friday at 13.00-14.00, the implementation is carried out in each class with the homeroom teacher. The implementation uses the Iqra method and a material guide book entitled Tahsin Guide to Recitations of the Qur'an and Tajwid Science. 3) The evaluation of this mentoring program includes written and oral tests to measure understanding and practice of Tajwid science, as well as end-of-semester evaluations and teacher training. Continuous testing ensures fluency in reading the Al-Qur'an, with additional testing before going to grade 8, this testing is carried out with PAI teachers. The tahfidz 7A class was created based on testing the memorization of juz 30 to support the memorization of students who are already fluent in reading the Al-Qur'an. 4) The Al-Qur'an mentoring program is supported by adequate infrastructure, appropriate methodology, and relevant handbooks, but is hampered by a lack of student practice. External support includes Koran recitation activities at the mosque, additional tutoring, and family support, while internal and external barriers include limited student abilities, cellphone use, low motivation at home, and lack of parental involvement. Abstrak. Penelitian ini bertujuan untuk mengetahui perencanaan, pelaksanaan, evaluasi, dan faktor pendukung serta penghambat dalam program mentoring di SMP PGII 1 Bandung. Metode yang digunakan adalah deskriptif kualitatif dengan teknik pengumpulan data melalui wawancara dan dokumentasi. Hasil penelitian menunjukkan bahwa program mentoring ini dapat meningkatkan kemampuan membaca Al-Qur’an melalui 1)perencanaan dibuat dengan tujuan untuk memberantas buta huruf Al Qur’an dan meningkatkan kemampuan membaca,menulis dan memahami Al Qur’an, serta menyusun jadwal waktu, tempat dan narasumber, 2) pelaksanaan dilaksanakan pada hari Jum’at pukul 13.00-14.00,pelaksanaan dilaksanakan di kelasnya masing masing bersama wali kelasnya. Pelaksanaan menggunakan metode Iqra dan buku panduan materi yang berjudul Panduan Tahsin Tilawah Al Qur’an dan Ilmu Tajwid. 3) Evaluasi program mentoring ini yaitu evaluasi mencakup tes tertulis dan lisan untuk mengukur pemahaman dan praktik ilmu tajwid, serta evaluasi akhir semester dan pelatihan guru. Pengetesan berkelanjutan memastikan kelancaran membaca Al-Qur'an, dengan pengetesan tambahan sebelum naik kelas 8 pengetesan tersebut dilakukan bersama guru PAI. Kelas tahfidz 7A dibuat berdasarkan pengetesan hafalan juz 30 untuk mendukung hafalan siswa yang sudah lancar membaca Al-Qur'an. 4) Program mentoring Al-Qur'an didukung oleh sarana prasarana yang memadai, metodologi tepat, dan buku pegangan relevan, namun terkendala kurangnya latihan siswa. Dukungan eksternal meliputi aktivitas mengaji di masjid, les tambahan, dan dukungan keluarga, sementara hambatan internal dan eksternal mencakup kemampuan siswa terbatas, penggunaan handphone, motivasi rendah di rumah, dan kurangnya keterlibatan orang tua.